Przesłuchanie w obecności psa wspierającego w postępowaniu karnym. Skuteczny środek ochrony pokrzywdzonych i świadków wrażliwych czy zagrożenie dla interesów oskarżonego i dobrostanu psa? - Klubińska, Maja (PRAWO i WIĘŹ, 2025)
For decades, national, international, and supranational legislators have shown interest in fighting for the rights of victims and witnesses in criminal proceedings, as reflected in numerous legal acts. Nevertheless, the need to find solutions that duly protect the interests of victims and witnesses while upholding the defendant's right to a fair trial remains relevant. For this reason, this article examines hearings conducted with the assistance of a facility dog as a means of supporting vulnerable victims and witnesses. This method, which is not part of the Polish criminal process, has been used for many years in other countries, particularly in the USA. Given this context, it was deemed advisable to conduct a detailed analysis and assess whether its inclusion in Polish criminal proceedings would be justified.